Law for sustainable soils: International and national aspects - Boer Ben (Glasnik Srpskog Geografskog Društva, 2010)
Work on the development of adequate international and national legal frameworks for sustainable soils has been underway for over a decade. Significantly, the initial drafting work on the need for an international convention or other instrument on soil came from the soil science community. In 1999, as a result of an approach from soil scientists to the IUCN Commission on Environmental Law a Specialist Group on Sustainable Soils and Desertification was established in order to investigate both international and national legal regimes to promote the sustainable use of soil. This paper looks at the development of an international legal instrument on sustainable soils, and explores the scope and range of possibilities for the form of such an instrument. It then canvasses the basic elements that should be included in the drafting of national of national legislation. It concludes by making some preliminary suggestions regarding the development of legal and institutional frameworks for soil management in Balkan countries.